The Blackademic Life : Academic Fiction, Higher Education, and the Black Intellectual - Porter, Lavelle (Book collections on Project MUSE., 2020)
This book critically examines academic fictions produced by black writers. The author evaluates academic literature as a space for Black writers to produce counternarratives that celebrate the potentials of Black intelligence and argue for the importance of Black higher education, particularly in the humanistic tradition. Beginning from an examination of W.E.B. Dubois's creative writing as the source of the first Black academic novels, the author looks at the fictional representations of Black intellectual life and the expectations that are placed on them to be racial representatives and spokespersons, whether or not they ever intended to be. The final chapter examines blackademics on stage and screen, including the 2014 academic film "Dear White People" and the law professor Viola Davis on the TV show "How to Get Away with Murder."--Description provided by publisher